Does Engaging Patients with Relevant Education About Long-Term Opioid Use Before Spine Surgery Affect Long-term Opioid Use? A Randomized Controlled Trial. Issue 1 (1st January 2022) - Rhon, Daniel I.; Greenlee, Tina A.; Gill, Norman W.; Carlson, Andrew E.; Hart, Allison M.; Larsen, Trent H.; McLelland, Alex; Mayhew, Rachel J.; McCafferty, Randall R.; Koppenhaver, Shane L.
Abstract : Study Design: Parallel-arm randomized controlled trial. Objective: To assess the effectiveness of an enhanced video education session highlighting risks of opioid utilization on longterm opioid utilization after spine surgery. Summary of Background Data: Long-term opioid use occurs in more than half of patients undergoing spine surgery and strategies to reduce this use are needed. Methods: Patients undergoing spine surgery at Brooke Army Medical Center between July 2015 and February 2017 were recruited at their preoperative appointment, receiving the singlesession interactive video education or control at that same appointment. Opioid utilization was tracked for the full year after surgery from the Pharmacy Data Transaction Service of the Military Health System Data Repository. Self-reported pain also collected weekly for 1 and at 6months. Results: A total of 120 participants (40 women, 33.3%) with a mean age of 45.9 ± 10.6 years were randomized 1:1 to the enhanced education and usual care control (60 per group). In the year following surgery the cohort had a mean 5.1 (standard deviation [SD] 5.9) unique prescription fills, mean total days' supply was 88.3 (SD 134.9), and mean cumulative morphine milligrams equivalents per participant was 4193.0 (SD 12, 187.9) within the year after surgery, with no significant differences in any opioid use measures between groups. Twelve individuals in the standard care group and 13 in the enhanced education group were classified with having long-term opioid utilization. Conclusion: The video education session did not influence opioid use after spine surgery compared to the usual care control. There was no significant difference in individuals classified as long-term opioid users after surgery based on the intervention group. Prior opioid use was a strong predictor of future opioid use in this cohort. Strategies to improve education engagement, understanding, and decision- making continue to be of high importance for mitigating risk of long-term opioid use after spine surgery. Level of Evidence: 1 Abstract : Patients were randomized to receive a single interactive opioid-education session versus usual care at their pre-operative appointment for spine surgery; then followed to assess incidence of long-term opioid use. There were no differences between groups. The majority of the cohort were prior opioid users, a strong predictor of long-term opioid use.